Análisis de la potencialidad turística e interacción del sistema turístico de la parroquia tendales, cantón El Guabo, El Oro, Ecuador. - Aponte Socola, Cindy Julissa; Galvez Vasquez, Joselyn Michelle (My University, 2020)
Tendales, is a parish of the canton El Guabo, province of El Oro, has a population of 5137 inhabitants in estimate of the 2010 census. Agriculture, livestock, fishing and tourism are the main economic activities prevailing in the parish. It has natural attractions, however it is unknown how the tourism system interacts in the territory, which leads to having as its main objective: to analyze the internal elements of the tourist system, as well as determine the tourist potential of the attractions; through the application of the Methodological Guide for the hierarchy of attractions, detecting the strengths and weaknesses that condition tourism development. An investigation was carried out based on a descriptive method, through the use of primary and secondary sources, with a qualitative and quantitative approach; whose research instruments were: direct observation, interviews and the Methodological Guide for the hierarchy of attractions, prepared by MINTUR. The results of this research reveal weaknesses in certain elements of the tourism system and in terms of the analysis of the tourism potential of the parish, it was determined that Bajo Alto is the attraction with the greatest potential, because it has the best facilities. While in the attractions "La Puntilla" and the "Isla de las aves" presented greater weaknesses that condition tourism; therefore, these weaknesses must be strengthened by working together, involving the community, service providers and the Decentralized Autonomous Government of the area.
Tendales, es una parroquia del cantón El Guabo, provincia de El Oro, posee una población de 5137 habitantes en estimación del censo 2010. Siendo la agricultura, ganadería, pesca y el turismo las principales actividades económicas predominantes de la parroquia. Posee atractivos de carácter natural, no obstante, se desconoce cómo interactúa el sistema turístico en el territorio, mismo que conlleva a tener como objetivo principal: analizar los elementos internos del sistema turístico, así como también determinar el potencial turístico de los atractivos; a través de la aplicación de la Guía metodológica para la jerarquización de atractivos detectando las fortalezas y debilidades que condicionan el desarrollo turístico. Se realizó una investigación basada en un método descriptivo, mediante el uso de fuentes primarias y secundarias, con un enfoque cualitativo y cuantitativo; cuyos instrumentos de investigación fueron: la observación directa, entrevistas y la Guía Metodológica para la jerarquización de atractivos, elaborado por MINTUR. Los resultados de esta investigación revelan debilidades en ciertos elementos del sistema turístico y en cuanto al análisis de la potencialidad turística de la parroquia, se determinó que Bajo Alto es el atractivo con mayor potencial, debido a que cuenta con las facilidades óptimas. Mientras que en los atractivos “La Puntilla” y la “Isla de las aves” presentaron mayores debilidades que condicionan el turismo; por ende, se debe fortalecer estas debilidades trabajando mancomunadamente, involucrando a la comunidad, prestadores de servicios y al Gobierno Autónomo Descentralizado de la zona.
Keywords: SISTEMA TURÍSTICO; DESARROLLO TURÍSTICO; DIAGNÓSTICO LOCAL; POTENCIALIDAD